1985
DOI: 10.1002/ajh.2830180409
|View full text |Cite
|
Sign up to set email alerts
|

Increased numbers of marrow basophils may be associated with a t(6;9) in ANLL

Abstract: We have characterized another subset of acute nonlymphocytic leukemia (ANLL) based on the cytogenetic and morphologic findings in a group of nine patients. Five patients had chromosomal analyses performed at the University of Chicago, two patients were studied at the All-Union Cancer Research Center in Moscow, and one patient each was studied at the University of Maryland and at Fairfax Hospital in Fairfax, Virginia. All nine patients had a reciprocal translocation involving the short arm of chromosome 6 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
1
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(44 citation statements)
references
References 27 publications
4
38
1
1
Order By: Relevance
“…[2][3][4]28,29 We also confirmed the high incidence of FLT3-ITD: 5/8 cases compared to nine out of 10 published cases. 27 It has been suggested that genomic instability in DEK-CAN 镁 blasts induces FLT3-ITD.…”
Section: Discussionsupporting
confidence: 75%
“…[2][3][4]28,29 We also confirmed the high incidence of FLT3-ITD: 5/8 cases compared to nine out of 10 published cases. 27 It has been suggested that genomic instability in DEK-CAN 镁 blasts induces FLT3-ITD.…”
Section: Discussionsupporting
confidence: 75%
“…Increased numbers of basophils occur in some cases AML containing either the t(6;9)(p23;q34) or chromosome 12p abnormalities. 3,4 In this report, we describe an unusual case of AML containing a cryptic t(8;21) involving the AML1 and ETO genes that was associated with marked bone marrow basophilia. To our knowledge, this represents the first reported association of marked basophilia with expression of the chimeric AML1-ETO protein.…”
Section: To the Editormentioning
confidence: 91%
“…1 MRD can be detected and quantified in peripheral blood either by the polymerase chain reaction (PCR) 2 or by immunophenotyping. 3 Since rising levels of disease can be demonstrated in bone marrow prior to clinical relapse, 4,5 we decided to determine whether rising levels could likewise be detected in the blood by PCR and whether the features of such molecular relapse in blood were such as to suggest that monitoring of blood may be of practical value. If answers to these questions were in the affirmative, then this would indicate that more extensive prospective studies of the value of monitoring of blood could well be important.…”
Section: To the Editormentioning
confidence: 99%
“…Cytogenetic abnormalities commonly known to be associated with basophilia in acute leukemia include t(8;21)(q22;q22), t(6;9)(p23;q34) and inv 3(q21;26.2) [1,7,8]. Ph ?…”
Section: Dear Editormentioning
confidence: 99%
“…It is infrequently observed in acute leukemia and its relationship with the leukemic process, associated cytogenetic or molecular abnormalities predisposing to basophilia are poorly understood. The known morphological categories of acute myeloid leukemia associated with basophilia include AML M2, M4 and acute basophilic leukemia [1][2][3][4][5]. The presence of basophilia in AML is usually indicative of myeloid blast crisis in CML (MBC-CML), and de novo a philadelphia positive AML (Ph ?…”
mentioning
confidence: 99%